Keamanan Informasi dalam Sistem Informasi Modern: Analisis Ancaman dan Upaya Pengamanan Berdasarkan Studi Literatur - Sucia Nurmadani; Nada Amal Ceria; Munawar Khalil; Muhammad Fariz Riski; Muhammad Ramzy Rasyad (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security is a critical aspect of modern information systems, as information assets are vulnerable to various cyber threats that may compromise confidentiality, integrity, and availability. Attacks such as phishing, malware, ransomware, data breaches, and network-based attacks continue to increase and pose serious risks to organizations and individuals. This study aims to examine the concepts, threats, and protection strategies in information security based on scientific literature. The research method used is a literature review by analyzing 20 references published between 2020 and 2025 related to information security, information system security, network security, cryptography, and risk management. The results indicate that effective information security requires an integrated approach involving technical controls, security policies, risk management, and user awareness.